PENGARUH KOMUNIKASI ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI ASTON BATAM HOTEL AND RESIDENCES - Iqbal, Muhammad; Wulansari, Nidia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: This research is motivated by the phenomenon of work productivity, which is suspected to be influenced by organizational communication barriers. The aim of this study is to analyze the influence of organizational communication on employee work productivity at Aston Batam Hotel and Residences. This research is a quantitative study with an associative causal (cause and effect) approach, employing a survey method to investigate the influence of organizational communication (X) on employee work productivity (Y) at Aston Batam Hotel and Residences. The population consists of employees at Aston Batam Hotel and Residences. Involving 77 respondents as participants, this research uses a saturated sampling method. Data is collected through validated and reliable questionnaires. Hypothesis testing is conducted using simple linear regression through SPSS version 26.00. The research findings indicate that Organizational Communication is assessed as adequate (68%), and the same applies to Employee Work Productivity (79%). Hypothesis testing reveals a significant influence of Organizational Communication on Employee Work Productivity, with an F value of 12.153 and a significance level of 0.000. The R square value is 0.128, demonstrating a significant relationship between the two variables.